Answer:
B. The Limit is 1
Explanation:
Use the sandwhich theorem. The limit at both end as x approaches 0 is equal to 1, therefore f(x) must be equal to 1 as well because it's sandwhich between the two intervals.
Solving the Limits of the Endpoint:
![\lim_(n \to 0) (x^2-x^4)/(x^2)=(0)/(0)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/aunsdgb71rm3hagij5rg33dk57edjgp0cx.png)
This is an in-determinant form so you must use L'Hopitals rule.
![\lim_(n \to 0) (x^2-x^4)/(x^2) \rightarrow \lim_(n \to 0) (2x-4x^3)/(2x) \rightarrow \lim_(n \to 0) (2-12x^2)/(2) =1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/51pvjcfkuiceedj04hovvk91in88nlv466.png)
![\lim_(n \to 0) {(1)/(4)x^3+1}=1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ddd20pzrg8qq3viqawftnr0qcmjqo0jfrm.png)